Crash deformation simulation of tubular structure to determine automotive centre of gravity - Hosseinabadi, Reza Afshar (2009)
In this study, the effects of crush behaviour of tubular structures have been investigated throughout simulation work. The axial crush was performed to predict the behaviour of tubular structures in terms of displacement of centre of gravity (COG) and mass moments of inertia (lyy and lxz ). Crush simulation includes two sections; close and open cross-sections respectively. In the case of close cross-sections, a displacement of COG of tubular structures with various polygonal cross-sections is numerically investigated under axial crush using program code of ANSYS/LS-DYNA. A subroutine is developed using this code to calculate the COG of deformed shape, during and after crush condition. The effect of wall thickness on displacement of COG is also investigated. Subsequently, a procedure to find real time COG of tubular structure during and after crush is developed. Base on this procedure, a macro is added in the frame work of ANSYS/LS-DYNA to study the deformation behaviour of tubular structure by the accurate criteria of COG,xxxx . Furthermore, the optimum number of edge of polygonal cross-section to have a reasonable symmetric deformed shape during crush is determined. It is found that the effect of number of polygonal edges on symmetric deformation of COG becomes more prominent as wall thickness of tubular structure decreases. The higher number of edges stabilizes the deformation shape. To examine the open cross-sections, the tubular structures with various Cee-shaped cross sections are numerically investigated. The subroutine used for the first section is performed again. Yet, the effect of wall thickness was also studied. Subsequently, the effect of opening angle of Cee becomes more prominent as the wall thickness of the structure decreases. As the thickness increases, displacement of the COG in crush direction almost stabilizes for all opening angle of Cee in the range of 100 − 900 degrees. Furthermore, variation of lyy of structure with thicker wall for different cases of applied mass is approximately identical. As a contribution to real application, Cee-shaped cross-sections with higher wall thicknesses can be used in the form of frame structures in automotive industry in order to reduce the overall weight of the structure and therefore, to save more energy. The study is the continue by incorporating a developed subroutine that added in the pre-processing module, in the frame work of ANSYS, distribution of the extra mass according to specific assigned COG and calculation the first bending and torsional natural frequencies of the simplified model in order to maximize these frequencies with final mass constraint was successfully investigated. It was found that adding the extra mass symmetrically about longitudinal axes of Body In White (BIW), higher values for first bending and torsional natural frequency is achieved.